Investigation of low voltage DC microgrid using sliding mode control - D. Sattianadan; G. R. Prudhvi Kumar; R. Sridhar; Kuthuru Vishwas Reddy; Bhumireddy Sai Uday Reddy; Panga Mamatha (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
As the requirement of power increases, the use of renewable energy resources has become prominent. The power collected from these energy resources needs to be converted using AC-DC or DC-DC converters. The control of DC-DC converters is a complex task due to its non-linearity in the converter introduced by the external changes such as source voltage, cable resistance and load variations. Converters are to be designed to obtain a well stabilized output voltage and load current for variable source voltages and load changes. Droop control method is the most abundantly used technique in controlling the parallel converters. The major limitations of the conventional droop control technique are circulating current issues and improper load sharing. The proposed work is to resolve these issues by integrating Sliding Mode Controller (SMC) with the converter in order to enhance the performance of DC microgrid. The entire control system was designed by taking the output voltage error as the control variables. Similarly, droop control with PI and PID were also performed and all these techniques were simulated and compared using MATLAB/Simulink. The experimental results show that the proposed sliding mode controller technique provides good overall performance and is suitable against variable voltage and load changes.